The Effect of Moon Phase on The Catch of Bigeye Tuna (Thunnus obesus) in Eastern Indian Ocean - Irwan Jatmiko; Bram Setyadji; Rani Ekawaty (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2016)
Tuna is one of the important export commodities to increase government income. One of economically important tuna species is bigeye tuna (Thunnus obesus) which has a proportion of 21% of the total production of large tuna group. The objective of this study was to investigate the effects of different moon phase on the catch of bigeye tuna (T. obesus) in Eastern Indian Ocean. Data collection was conducted by the scientific observers from August 2005 to June 2014 in the tuna longline vessels were based in the port of Benoa, Bali. Moon phase data were collected from August 2005 to June 2014 from National Aeronautics and Space Administration (NASA). Catch data were calculated using the catch rate formula which defined as the number of catches per 100 hooks. The number of catch rate then was sorted into each moon phases and were analyzed using one-way Anova. This study covered 62 trips and 1,480 numbers of operations or sets was conducted from sampled vessels. The result showed that the average catch rate of bigeye tuna differed significantly among the moon phases. Tukey post-hoc tests showed that the average catch rate at full moon was the highest among the groups with around 0.3/100 hooks. This study showed that moon phase had significant effect on the catch of bigeye tuna (T. obesus) that increased the catch during full moon. Keywords: moon phase, catch rate, Eastern Indian Ocea, tuna, Thunnus obesus